Prioritization of Effective Strategic Parameters in the Removal of VOCs from the ROP System by Using AHP: A Case Study of Abadan Oil Refinery - Ladan Khajeh Hoseini; Reza Jalilzadeh Yengejeh; Ali Mahmoudie; Maryam Mohammadi Rouzbehani; Sima Sabz Alipour (Shiraz University of Medical Sciences, 2021)
Background:The spread of urbanization and industrialization, as well as changes in lifestyle and consumption patterns in recent years, especially in developing countries, has led to the production of huge volumes of pollution in urban and industrial areas. How to plan and manage them is one of the issues and problems in the world today. And if the environment is not taken into account at the same time as the industrialization of a society, not only will economic development not be achieved, but there will be many problems so that sometimes the long-term benefits of an industry are spent on compensation. Methods: The isa descriptive-analyticalstudy. Various steps were taken, including the results of statistical analysis, Delphi questionnaires, analysis of validity and reliability of the research, and extraction of influential factors affecting the performance of the ROP unit of Abadan Oil Refinery in 2019 until 2020. Finally, the results of weighting and ranking of effective strategic parameters in decision-making, decision-making and policy-making processes of different items including factors (components), criteria, sub-criteria, and strategic plans are presented. Using Expert Choice 2000 software, we weighed the parameters, and Cronbach's alpha was determined to be 0.932. Results: The results of weighting and ranking of effective strategic parameters in the decision-making process and policymaking of various items are presented.Finally, the component of human environment around the refinery with a weight priority of 0.288 in the first rank, the component of natural environment, the HSE component of the refinery with a weight of 0.244 in the second rank, and the components of technical characteristics and conditions of the refinery with a weight of 0.112 were in the third place. Conclusion:In this case study, we found thatthe greatest need for management was specific to the human environment, such as land use and development plans around the refinery, and the state of air and soil pollution and water resources.